EFFECT OF FABRIC STRUCTURE ON RIB FABRIC PROPERTIES - Anwarul Azim, Abu Yousuf Mohammad; Islam, Md. Ariful; Morshed, Monjur; Sarker, A.B.M. Yousuf; Haque, A. K. M. Monjurul; Khandakar, Firoze (European Scientific Journal, ESJ, 2014)
In this work,1×1Rib,1×1Skeleton rib, 2×2English rib, 2×2Swiss rib, 6×3Derby rib were produced with 20/2 Ne and 32/2 Ne combed ring yarn and V-bed knitting machine of 14 Gauge. In addition, Wales per 3cm, Course per 3cm, Stitch density, Stitch length, Tightness factor, GSM, Dimensional Stability of fabric were tested. According to test result, Wales per 3cm, Stitch density, Cover factor, GSM of 1×1Rib were higher than the 1×1Skeleton rib;Wales per 3cm, Course per 3cm, Stitch density, Stitch length, Cover factor, Shrinkage%, extension% of 2×2English rib were higher than the 1×1Rib; Wales per 3cm, Stitch density, GSM, Shrinkage%, extension% of 2×2Swiss rib were higher than the 1×1Rib; in 6×3Derby Rib values of the properties were higher than other structure; shrinkage and extension percentage increase with the increase of needle drop in knitting.